2023
DOI: 10.3390/jcs7040132
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Flexural Behaviour of Sustainable Reinforced Concrete Beam with a Smart Mortar Layer

Abstract: This paper deals with an experimental study of the flexural behavior of sustainable reinforced cement concrete (RCC) beams with a smart mortar layer attached to the concrete mixture. In total, nine RCC beams were cast and tested. Two types of reinforced concrete beams were cast, and three different beams of sizes 1000 × 150 × 200 mm and six different beams of sizes 1500 × 100 × 250 mm were considered. The flexural behavior of these RCC beams was studied in detail. The electrical resistivity of these beams was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Kim et al [104] reported a maximum sensing response of 2% for 10 mm thick MWCNT-based coatings within a stress range of 30% of flexural strength. Durairaj et al [103] obtained FCR values of between 10% and 15% for a strain range similar to the one investigated in this study by employing a 6 mm deep mortar layer with various combinations of brass and carbon fibre. Wen and Chung [101] obtained a maximum FCR amplitude of 0.15% on the tension side for a 5 mm thick coating with 0.5 wt% added carbon fibre for a beam deflection of about 0.09 mm.…”
Section: Electromechanical Testingsupporting
confidence: 70%
See 1 more Smart Citation
“…Kim et al [104] reported a maximum sensing response of 2% for 10 mm thick MWCNT-based coatings within a stress range of 30% of flexural strength. Durairaj et al [103] obtained FCR values of between 10% and 15% for a strain range similar to the one investigated in this study by employing a 6 mm deep mortar layer with various combinations of brass and carbon fibre. Wen and Chung [101] obtained a maximum FCR amplitude of 0.15% on the tension side for a 5 mm thick coating with 0.5 wt% added carbon fibre for a beam deflection of about 0.09 mm.…”
Section: Electromechanical Testingsupporting
confidence: 70%
“…It was conjectured that greater strain transmission occurred in thinner coatings, thus leading to a greater gauge factor. Likewise, Durairaj et al [103] applied carbon fibre and brass fibre mortar coatings to concrete beams under flexural bending for damage detection while employing different coating attachment methods; although a dependency between the electrical properties and the applied load was evident, the strain-sensing sensitivity was not calculated. Moreover, Kim et al [104] investigated the sensing behaviour of multi-walled carbon nanotube (MWCNT)-cement repairs under bending, and while a change in electrical properties under a load was observed, the sensing coefficient of the repairs was not determined.…”
Section: Coating Applicationsmentioning
confidence: 99%
“…It was found that the mechanical properties and durability of granite pulver self-curing selfcompacting concrete mixture can be improved through the optimal replacement of cement by granite pulver. Durairaj et al (2023) conducted an experimental study of the flexural behavior of sustainable reinforced cement concrete beams with a smart mortar layer attached to the concrete mixture. It was found that structural members can be coated with either carbon or brass fibers in thin mortar layers to detect damage to the member.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of concrete, such as tensile strength, compressive strength, exural strength, and modulus of elasticity, are essential metrics for evaluating its behaviour under various loads and environmental conditions [41], [42], [43], [44]. Tensile strength determines the concrete's capacity to resist tensile (stretching or pulling) forces, whereas compressive strength measures its ability to withstand compression.…”
Section: Introductionmentioning
confidence: 99%